Prognostic significance of copy number alterations detected by multi-link probe amplification of multiple genes in adult acute lymphoblastic leukemia - Fang, Qiuyun; Yuan, Tian; Li, Yan; Feng, Juan; Gong, Xiaoyuan; Li, Qinghua; Zhao, Xingli; Liu, Kaiqi; Tang, Kejing; Tian, Zheng; Zhang, Qi; Wang, Ying; et al. (Oncology letters, 2018)
The multiplex ligation-dependent probe amplification (MLPA) method was used to detect the copy number alterations (CNAs) of IKAROS family zinc finger 1 (IKZF1), paired box 5 (PAX5), ETS variant 6 (ETV6), RB transcriptional corepressor 1 (RB1), BTG anti-proliferation factor 1 (BTG1), early B-cell factor 1 (EBF1), cyclin dependent kinase inhibitor 2A/2B (CDKN2A/2B) and cytokine receptor like factor 2 (CRLF2) genes in 87 adults with acute lymphoblastic leukemia (ALL) in China. The effects of CNAs on prognosis were analyzed. Gene deletions were detected in 58/87 (66.7%) ALL patients. The most common deletions were observed in the following genes: IKZF1 (40.6%), CDKN2A (31.9%), CDKN2B (29%), PAX5 (21.7%), RB1 (14.5%) and BTG1 (10.1%). B cell-ALL (B-ALL) patients with CDKN2A/2B deletions exhibited poor 2-year overall survival (OS; P=0.055) and relapse-free survival (RFS; P=0.054) rates. CDKN2A/2B deletions were associated with poor 2-year OS (P=0.045) and RFS (P=0.071) rates in Philadelphia chromosome positive (Ph+) B-ALL patients, as well as in the high risk (HR) B-ALL group (P=0.037 and P=0.047, respectively). Patients with PAX5 deletions displayed poor 2-year OS (P=0.004) and RFS (P=0.016) rates in Philadelphia chromosome negative (Ph−) B-ALL patients. Patients with ≥3 gene deletions exhibited a poorer prognosis than other patients (OS, P=0.001; RFS, 0.002).